Moringa oil-based nanocarrier system containing curcumin formulation as anti- breast cancer agent: Efficacy and safety study - Widodo, Ferri; Anggadiredja, Kusnandar; Amalia, Riezki; Rachmawati, Heni (Narra Sains Indonesia, 2025)
Current anti-breast cancer drugs have limited efficacy and often cause severe side effects, highlighting the need for bioactive agents that could overcome these limitations. Curcumin, a phenolic compound from Curcuma domestica, has antineoplastic activity but has low solubility in physiological media, while moringa oil is a key component of the oil-phase nanocarrier and also possesses anticancer properties. The aim of this study was to develop a moringa oil-based nanocarrier system containing curcumin and to analyze its anticancer effects on MDA-MB-231 cell lines, focusing on the underlying mechanisms involving B-cell lymphoma 2 (Bcl-2) and Bcl-2-associated X (Bax) proteins. Additionally, the study investigated the side effects of the nanocarrier system following acute administration in animals. The anticancer effects were evaluated in vitro using MDA-MB-231 cell lines, while the acute toxicity assessment was conducted in healthy female Wistar rats. The nanocarrier system was formulated using moringa oil, Cremophor RH40, and PEG 400. Its cytotoxicity against MDA-MB-231 cells was assessed using the 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) assay. DNA fragmentation, apoptosis, and the expression of Bax and Bcl-2 proteins were analyzed via terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) assays, flow cytometry, and western blotting. Acute toxicity was further evaluated in female Wistar rats. The results demonstrated that the moringa oil-based nanocarrier system containing curcumin inhibited cell proliferation and induced apoptosis in MDA-MB-231 cells. Curcumin suppressed tumorigenesis by modulating Bcl-2 and Bax protein expression. Our data indicated that the combination of curcumin and moringa oil in a nanocarrier system had greater anticancer potential than either component alone. Moreover, administration of the nanocarrier system did not result in any clinically significant changes in body weight, behavior, or organ weight indicative of toxicological effects. No treatment-related histopathological abnormalities were observed at terminal necropsy. In conclusion, this novel combination of curcumin and moringa in nanocarrier system has better anticancer potential; nevertheless, further studies are needed to confirm this in cancer animal models.